Geographic Information System Mapping Of Criminality Villed Areas In Lhokseumawe Using K-Means Method - Risawandi Risawandi; Yesy Afrillia (Universitas Medan Area, 2022)
Crime is a serious problem that can have a wide impact on all levels of society. Every day criminal acts can occur anywhere, especially in big cities, including Lhokseumawe, it is difficult for the community to determine the locations of areas prone to crime and the locations of safe areas. As a solution to the problem, a map of crime-prone areas is needed to show and display the location of these areas. To assist the mapping process of areas prone to crime, a Geographical Information System is needed with criminal data in the form of fraud, theft, gambling, torture and rape obtained from the Lhokseumawe Police, for the classification process of the level of vulnerability of an area the K-Means method is used, and Openstreetmap and QuantumGis are used for mapping of the classification of areas prone to crime. The results of this study are a Geographical Information System which can display the results of an interactive classification of crime-prone areas in the form of a map and can be accessed by related parties to determine the level of crime vulnerability, then from the public's side can find out the location of crime-prone areas in lhokseumawe so that it becomes an initial reference for action anticipation.